Chronic inguinal pain after laparoscopic intraperitoneal onlay mesh (IPOM) repair for inguinal hernia treated successfully with laparoscopic selective neurectomy: A case report. (2017) - Hanada, Keita; Narita, Masato; Goto, Kentaro; Okada, Haruka; Okura, Keisuke; Jikihara, Shunpei; Nakanishi, Hiroki; Saji, Masashi; Matsusue, Ryo; Hata, Hiroaki; Yamaguchi, Takashi; Otani, Tetsushi; et al.
Highlights: Laparoscopic IPOM repair for inguinal hernia may cause chronic neuropathic pain. Laparoscopic IPOM repair for inguinal hernia should be avoided as much as possible. Laparoscopic selective neurectomy is an option for chronic neuropathic pain. Abstract: Introduction: Laparoscopic intraperitoneal onlay mesh (IPOM) repair is occasionally used for inguinal hernia repair. Here, we report a case of chronic neuropathic pain after laparoscopic IPOM repair for inguinal hernia, which was treated successfully with laparoscopic selective neurectomy. Presentation of case: A 59-year-old man with bilateral inguinal hernia underwent laparoscopic repair. Transabdominal preperitoneal repair was performed on the left side, whereas IPOM repair was performed on the right side due to a peritoneal defect. At postoperative month 1, he presented with severe pain and numbness distributed from the right inguinal region to the inner thigh region. The symptoms had persisted for 1 year despite medical treatment. We diagnosed that the symptoms might be due to the entrapment of nerves in the contracted mesh, and performed a second surgery via laparoscopic approach 13 months after the first surgery. On laparoscopic exploration, the lateral side of the mesh was contracted and involved nerve branches. We ligated and cut off these nerve branches. His symptoms resolved immediately after the surgery. At postoperative month 12, he has passed without any pain, numbness, and hernia recurrence. Discussion: Laparoscopic exploration would be useful to figure out chronic neuropathic pain after laparoscopic inguinal hernia repair. Conclusion: Laparoscopic IPOM repair for inguinal hernia should be avoided as much as possible because it may cause chronic neuropathic pain. Laparoscopic selective neurectomy is an option for patients with chronic neuropathic pain after laparoscopic hernia repair.